2014
DOI: 10.3389/fnsys.2014.00215
|View full text |Cite
|
Sign up to set email alerts
|

EEG slow-wave coherence changes in propofol-induced general anesthesia: experiment and theory

Abstract: The electroencephalogram (EEG) patterns recorded during general anesthetic-induced coma are closely similar to those seen during slow-wave sleep, the deepest stage of natural sleep; both states show patterns dominated by large amplitude slow waves. Slow oscillations are believed to be important for memory consolidation during natural sleep. Tracking the emergence of slow-wave oscillations during transition to unconsciousness may help us to identify drug-induced alterations of the underlying brain state, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 70 publications
(94 reference statements)
3
13
0
Order By: Relevance
“…2b). These observations under propofol are consistent with previous reports (Chennu et al, 2016; Feshchenko et al, 2004; Ni Mhuircheartaigh et al, 2013; Purdon et al, 2013; Supp et al, 2011; Tinker et al, 1977; Wang et al, 2014) and some have suggested that changes in frontal alpha and delta power are reliable indicators of loss of consciousness under propofol (Purdon et al, 2013). However, a recent study using the isolated forearm technique challenges the reliability of such an approach (Gaskell et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…2b). These observations under propofol are consistent with previous reports (Chennu et al, 2016; Feshchenko et al, 2004; Ni Mhuircheartaigh et al, 2013; Purdon et al, 2013; Supp et al, 2011; Tinker et al, 1977; Wang et al, 2014) and some have suggested that changes in frontal alpha and delta power are reliable indicators of loss of consciousness under propofol (Purdon et al, 2013). However, a recent study using the isolated forearm technique challenges the reliability of such an approach (Gaskell et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…This is a remarkable result considering the differences in methodological (and arbitrary) choices we used to harmonize the analysis pipelines of the aforementioned studies. For the biomarkers for which we failed to observe a significant effect (PLV and sdDTF) this failure could be indeed related to different signal processing pipelines regarding the epoch length 69 , the reference montage 70,71 , the different state of vigilance [72][73][74] .…”
Section: Discussionmentioning
confidence: 90%
“…In this regard most studies of anaesthetic-induced changes in consciousness, infer this state from changes in behavioural responsiveness 1 , 2 . Reversible changes in consciousness, based on responsiveness, appear to correlate with changes in slow wave activity, measured by recording the power between 0.5 and 4 Hz (delta activity) 3 , 4 . In other words, it is well known the delta activity is a typical feature as a signature of unconsciousness 5 .…”
Section: Introductionmentioning
confidence: 99%